Analyzing routes in Ottoman Greater Syria using historical GIS: The 1849 Saida map. Issue 5 (15th July 2021) - Zohar, Motti; Ben‐Bassat, Yuval
Abstract: Ottoman cartographic materials are important sources of information on 19th and early 20th‐century Greater Syria. However, large portions of this corpus have yet to be examined. This study explores a rare mid‐19th‐century Ottoman map of the Province of Saida preserved in the Ottoman Archive in Istanbul. It lists travel times between villages, towns, and administrative centers in Greater Syria under Ottoman rule, and shows the network of routes connecting these localities. Using an historical GIS approach, we evaluated the characteristics of the map and its cartographical accuracy and merits. The network of routes on the map is compared to route reconstructions based on least‐cost‐path principles. The discussion focuses on the historical context of the map and the ways in which it reflects the strength of Ottoman rule and familiarity with Greater Syria at the time.